Developing interactive materials of writing non-literary texts based on flipbooks for secondary school students - Yuni Hajar; Elly Prihasti Wuriyani; Muhammad Joharis Lubis (JOALL (Journal of Applied Linguistics and Literature), 2023)
This study aims to produce and determine the effectiveness of interactive material for writing non-literary texts based on flipbooks for class X students of MAN 2 Langkat. This research is a Research and Development (RnD) research using the ADDIE development model. There are three subjects in this development research. The first, validators consist of two material experts and two design experts. The four validators are Postgraduate Lecturers at Medan State University. Second, two teachers of Indonesian subjects. And the last are the students of class X MAN 2 Langkat totalled 96 people from three different classes, namely X MIA, X IIS, and X IIA. The data collection instruments used were in the form of a teacher needs analysis questionnaire, a student needs analysis questionnaire, a material and media expert validation sheet, a teacher validation sheet, and a student response sheet. Individual trials obtained "good" criteria with an average percentage of 88.5%. The small group trial obtained the criteria of "very good" with an average percentage of 89.8%. The wider trial obtained the criteria of "very good" with an average percentage of 89.5%. The effectiveness of the interactive material for writing non-literary texts based on flipbooks developed shows higher student learning outcomes with an average pre-test score of 73.4% with the lowest score being 62, and the highest score being 82. While the post-test average score -test is 86.7% with the lowest score is 75 and the highest score is 94. Based on these data, it can be concluded that the interactive material for writing non-literary texts based on flipbooks is effective and can improve student learning outcomes, especially in writing non-literary texts.